The masses of local group dwarf spheroidal galaxies: the death of the universal mass profile - Collins, Michelle; Koch-Hansen, Andreas (The astrophysical journal, 2014)
We investigate the claim that all dwarf spheroidal galaxies (dSphs) reside within halos that share a common, universal mass profile as has been derived for dSphs of the galaxy. By folding in kinematic information for 25 Andromeda dSphs, more than doubling the previous sample size, we find that a singular mass profile cannot be found to fit all of the observations well. Further, the best-fit dark matter density profile measured solely for the Milky Way d Sphs is marginally discrepant with that of the Andromeda dSphs (at just beyond the 1σ level), where a profile with lower maximum circular velocity, and hence mass, is preferred. The agreement is significantly better when three extreme Andromeda outliers, And XIX, XXI, and XXV, all of which have large half-light radii (≳ 600 pc) and low-velocity dispersions (σ v < 5 km s-1), are omitted from the sample. We argue that the unusual properties of these outliers are likely caused by tidal interactions with the host galaxy.
Gesehen am 12.08.2020